Penerapan Model Pembelajaran PjBL untuk Meningkatan Keterampilan Menulis Paragraf pada Mata Pelajaran Bahasa Indonesia di Kelas IVA SDN 187/II Kuning Gading - Dea Vista Febrianika; Trikinasih Handayani; Dewi Partini (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
This research is motivated by the identification of a fairly broad problem, so the actions taken need to limit the problem of students' paragraph writing skills in learning Indonesian. This study aims to apply the steps of the project based learning model to improve paragraph writing skills in Indonesian subjects in class IVa SDN 187/II Kuning Gading. This research was conducted in class IVa, which consisted of 20 students, consisting of 14 girls and 6 boys. The design used in this research is classroom action research (CAR) using two cycles, each cycle consists of; (1) action planning, (2) action implementation, (3) observation, (4) reflection. Methods of data collection using observation and tests. The instruments used in this study were student activity sheets and student writing skills assessment sheets. The data obtained were analyzed using qualitative and quantitative analysis. The results of this study indicate that the use of the Project Based Learning (PjBL) learning model can improve the paragraph writing skills of class IVa students. The average value of paragraph writing skills in Cycle I was 72.02% with learning outcomes of 74.00%, then in Cycle II the average value of paragraph writing skills was 85.66% with learning outcomes of 86.00%.